STUDENTS’ VOCABULARY ACHIEVEMENT UNDER WORDWALL MEDIA AT SMP NEGERI 23 MAKASSAR - Merdeka Wati; Restu Januarty (Publikasi dan UKI Press UKI Toraja., 2022)
This research aimed to find out whether or not the used of word wall media can improve students’ vocabulary mastery. The writer used pre-experimental design which involved one class as the subject of the research. The population was VIII grade students at SMP Negeri 23 Makassar. Sample in this research was class VIII.1 which consists of 35 students. In this research the writer gathering data by given vocabulary test in pre-test and post-test consist of 10 multiple choice questions and 10 matching word questions. Pre- test is given to find out how far the students ability before they were given treatment used word wall media. The writer gave the posttest to know the student’s improvement after they are given treatment. The writer analyze data to find the mean score, the different between pre-test and post-test used statistic formula. The result of the research showed that there was a significant different which gained by the students in pre-test and post-test. The mean score of in pre-test is 59.43 and post- test is 80.14. From the result of data analyze, it can be concluded that by using word wall as a media can improved students vocabulary mastery at SMP Negeri 23 Makassar.